The Novel Work Environment Model to Improve Teacher Performance: A Study at SMAN 1 Sungkai Jaya, North Lampung - Nitalinda, Desy; Abdurrahman, Abdurrahman; Hariri, Hasan; Sowiyah, Sowiyah; Karwan, Dedy Hermanto; Rahman, Bujang (Jurnal Pendidikan Progresif, 2019)
The Novel Work Environment Model to Improve Teacher Performance: A Study at SMAN 1 Sungkai Jaya, North Lampung. Objectives: This study aims to create a good environment in order to improve teacher performance in SMA Negeri 1 Sungkai Jaya, North Lampung. In this study, a combination of two aspects of the work environment model was carried out to create a reflective and appropriate work environment model. Methods: This study uses qualitative methods with 50 respondents. Data collection techniques were carried out through observation, interviews, documentation, and Focus Group Discussions (FGD). Findings: The results showed that the social environment at SMAN 1 was good enough to produce good teacher outcomes, but improving communication caused discomfort between the teacher and school principal relations. The artistic environment at SMAN 1 shows that the teachers in carrying out the assignments given by the principal are going well, in an orderly and disciplined manner, but the quality of the learning tools is better than the difficulties in time. Conclusions: Model The reflective work environment has a good status on the relationship between the principal and the teacher because the teacher and the principal are not directly related. Keywords: Reflective work environment model, school, teacher performance. DOI: http://dx.doi.org/10.23960/jpp.v9.i2.201906